Cash or card: consumer perceptions of payment modes - Khan, Jashim (Auckland University of Technology, 2011)
This study examines the cognitive and emotional associations that people have with payment modes in order to ascertain if and how these associations impact on payment mode choice and how the payment mode selected impacts on purchase behaviour. This is a neglected research area, but not totally ignored. Early research compared cash, cheque and credit card payment modes and concluded that credit card use equates with increased spending. Whether the change is due to access of credit or the absence of cash is not wholly ascertained. The absence of cash implies that the physicality of the mode may have a bearing on purchase decisions. Both modes of payment lack ‘transparency’. This research examines the underlying reasons for the physicality factor and finds evidence that the physicality of notes and coins affect perceptions, judgements and behaviours. This study is a multi-phase, multi-method field based naturalistic enquiry. Modes of data collection included focus groups and in-depth interviews; a quasi field experiment and a self report scale. Nvivo was used to analyse focus group data to develop items for a payment mode perceptions (PMP) scale. Data from the field study employs ANOVA technique to examine modes of payment effect on purchase behaviour. The result indicates that the payment mode has significant effect on value and volume of purchase. Participants who used debit cards spent significantly higher than did the cash group. Participants who preferred to and normally used cash or debit card exhibited positive feeling to their preferred payment mode. However irrespective of their preferred mode, participants did not like gifts of money deposited to their bank accounts, thought that their awareness of spending and money management skills were impair by electronic card use.
Keywords: Cash; Debit cards; Payment modes; Mental accounting; Anchoring; Embodied cognition; Payment mode perceptions; Scale development; Mixed method research design